Father–Son Communication: An Intervention Strategy for Boys and Men of Color to Promote Neighborhood Safety Post-Ferguson. Issue 2 (June 2016) - Johnson, Waldo E.; Rich, Lauren M.; Keene, Lance C.
Compared with their White counterparts, preadolescent and adolescent males of color are disproportionately exposed to violence from multiple sources, including law enforcement, neighborhood community violence, and racially motivated attacks. Existing preventive and intervention strategies have primarily focused on the policing and/or reformation of individual youth. Alternatively, this article draws on both social-ecological and risk and resilience frameworks to argue for the mobilization of fathers, social fathers, and their sons of color, in a communication intervention strategy that enhances father–son communication about successful navigation of diverse neighborhood contexts post-Ferguson. Such an intervention may improve individuals' outcomes and neighborhood collective efficacy by strengthening fathers' and sons' engagement in their roles in families, neighborhoods, and communities.